2014
DOI: 10.1111/wre.12086
|View full text |Cite
|
Sign up to set email alerts
|

Site‐related set‐back by weeds on the establishment of 12 biomass willow clones

Abstract: Ten commercial clones of willow and two breeding clones were studied for their ability to compete with weeds during the establishment year at three different sites in southern Sweden. Cuttings were planted according to commercial practice in April, and the two treatments, 'Weeded' and 'Unweeded', were laid out in a strip-plot design. Weeds in the 'Weeded' treatment were removed mechanically and by hand hoeing. Willow plant shoot weight and plant mortality were measured after the first growing season to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
2
27
2
Order By: Relevance
“…The preparation, planting, management and local conditions of the three trial sites (J, P and S) and the pedigree of the clones are described in detail in a previous paper [8]. That paper focuses on the establishment year whereas this paper mainly focuses on the two subsequent growing seasons.…”
Section: Management and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation, planting, management and local conditions of the three trial sites (J, P and S) and the pedigree of the clones are described in detail in a previous paper [8]. That paper focuses on the establishment year whereas this paper mainly focuses on the two subsequent growing seasons.…”
Section: Management and Experimental Designmentioning
confidence: 99%
“…If differences exist between willow clones in weed competitive ability it would be possible to select for this trait during breeding. Albertsson et al [8] found only small differences in weed tolerance between 12 willow biomass clones during the establishment year. In other crops such as wheat [12], soybean [14] and maize [15], there are differences between cultivars in their ability to compete with weeds.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the start of the experiment the rods were divided into cuttings of 20 ± 0.1 cm in length as long as their diameter was more than 7 mm and their location along the rod in terms of position from the ground (1)(2)(3)(4)(5)(6)(7)(8), number of visible buds on the bark and diameters of the apical cutting part were recorded and the cutting was marked using a waterproof pencil. In total, 120 cuttings per clone in 2009 and 60 cuttings in 2010 were made.…”
Section: Methodsmentioning
confidence: 99%
“…It is especially important to ensure fast, equal sprouting of cuttings with consecutive rapid shoot growth occur during the first growing season of SRC, since this is the period where the largest seed bank of weed species in the plantation soil exists and competition between sprouting cuttings and weeds can be expected [5][6][7]. Therefore, a lot of attention has been paid to the study of critical factors that may impact the growth potential of cuttings [8].…”
Section: Introductionmentioning
confidence: 99%